A Buddhist Approach to Death and Its Lesson - Das, Sanjib Kumar (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Buddhism says that life is a confluence, a cycle of birth and death. This cycle is called saṃsāra. Such life and death of every living being as a continuum, believing that consciousness continue after death and will be reborn. The early four incidents occurred in Buddha’s life that motivated him to renounce household life are the best examples to understand death. Objective: The objective of the paper is to explain that human body is consisted of five aggregates. As long as we have these aggregates we have to undergo the sufferings including death. Methodology: Library based analytical approach has been employed to carryout this research. Result: Through the study human body is found to be consisted of five aggregates. Suffering is inevitable as long as we have these aggregates. Death is unavoidable. Meditation is key to lead humans free from death and suffering. Upon doing practice it in a precise and unmistaken way one is engaged in unmistaken śamatha and vipaśyanā to uplift humankind from the bondage of Samsara. Conclusion: Death is certain to happen and it has three reasons for this certainty: one must die because there is no one who has not died before, the body is composite, and life ebbs from moment to moment. In addition to these three, the time of death is uncertain because some die in the womb of mother, some just after birth, some at young age and so on. This death has two main divisions, three main causes: Process of ceasing sense powers at the time of death and process of dissolutions of elements of the time of death. Similarly, the experience which beings have at the time of death varies. However, there is certainly a way to be free from this unwanted suffering of death and that can be possible upon following the prescribed path beginning with the mindfulness of death as expounded by the Buddha and his successors.